Relationship between take-off motion and jump distance in medium-hill ski jumping - Funato, Y.; Sakurai, S. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this study was to identify the relationship between take-off motion and jump distance in medium-hill ski jumping. The subjects were 21 ski jumpers (16 males and 5 females, height: 1.65±0.09 m, weight: 54.6±8.9 kg, age: 19.2±6.8 yr) whose take-off phase on a medium-hill (hill size: 68 m) was filmed with two synchronized high-speed video cameras (200 Hz). The take-off motion was analyzed two-dimensionally in the sagittal plane. The results were as follows: 1) The approach velocity and vertical velocity of the jumper's center of gravity at the instant of release were found to be significantly correlated with jump distance (r=0.768, p<0.01; r=0.775, p<0.01), suggesting that these two parameters are as important for medium-hill as for normal-hill ski jumping. 2) Ski jumpers increased their jump distance by moving their trunk forward with knee joint extension during take-off and by reducing the trunk angle at the instant of release from an initial position in which the lower limb joints were deeply flexed. 3) Stepwise multiple regression analysis showed that (1) the hip angle at the initial position, (2) the knee joint angular velocity at the instant of release, and (3) the horizontal velocity of the trunk relative to the feet at the instant of release were the three significant factors, accounting for 82.3% of the jump distance. The importance of knee joint angular velocity at the instant of release has increased following the recent changes in ski jumping technique and regulations.